The Ecological Role of Sharks on Coral Reefs. (May 2016) - Roff, George; Doropoulos, Christopher; Rogers, Alice; Bozec, Yves-Marie; Krueck, Nils C.; Aurellado, Eleanor; Priest, Mark; Birrell, Chico; Mumby, Peter J.
Abstract : Sharks are considered the apex predator of coral reefs, but the consequences of their global depletion are uncertain. Here we explore the ecological roles of sharks on coral reefs and, conversely, the importance of reefs for sharks. We find that most reef-associated shark species do not act as apex predators but instead function as mesopredators along with a diverse group of reef fish. While sharks perform important direct and indirect ecological roles, the evidence to support hypothesised shark-driven trophic cascades that benefit corals is weak and equivocal. Coral reefs provide some functional benefits to sharks, but sharks do not appear to favour healthier reef environments. Restoring populations of sharks is important and can yet deliver ecological surprise. Trends: Stable isotopes reveal that sharks span an extended range of trophic levels with true apex species being higher than most common reef sharks. Dietary analysis reveals that most common reef sharks are mesopredators occupying a similar trophic level to large piscivorous fishes. Evidence for shark-induced trophic cascades that benefit herbivorous fishes is weak or equivocal on coral reefs. Sharks can exert non-consumptive or 'fear' effects that disrupt the foraging of potential prey. While coral reefs provide a range of ecological benefits for sharks, the link between healthy reefs and shark abundance is unclear.